Collaborative learning within Malaysian's Education System / Hazmi Rohaini Makhtar - Makhtar, Hazmi Rohaini (2004)
Rapid change in information technology has led to changes in the way we learn. Our education has been shifted from traditional book-based classroom learning to a virtual classroom where student who are remotely located can collaborate, thus share their knowledge and ideas with each other. Communication tools such as e-mail, chat, bulletin board and virtual forum serve as main tool for learning and teaching. In this project, the above mentioned technology, namely collaborative learning was proposed to enable expatriate Malaysian student particularly secondary school students to pursue with Malaysian's Education System. Besides taking foreign syllabus of education, they were giving an opportunity to continue with their homeland education system. In addition to that, a prototype of e-coUaborative will be developed. Element of collaborative learning as well as good user interface design with regard to human computer interaction will be adapted. Apart from that, a standard document for requirement specification in developing the prototype will also be produced. Students from international school were among targeted respondent to materialize the study. All the data gathered were tabulated and analyzed using SPSS program. It is hoped that collaborative learning can benefited expatriate Malaysian students and contribute some significant to our education system.